Urinary concentrations of arsenic species in older Dutch adults and risk of chronic kidney disease - Hannah P. McKeon; Weiluan Chen; Jan Dirk te Biesebeek; Nanette G. Vrijenhoek; Jacqueline J.M. Castenmiller; Marcel J.B. Mengelers (Environment International)
Chronic exposure to arsenic (As) is associated with various cancers and nephrotoxicity. It occurs in different chemical forms which vary in toxicological potential. Human biomonitoring (HBM) is used to measure internal (all-route) exposure to different As species. To assess the risk of internal As exposure, toxic relevant arsenic (TRA) (sum of arsenite (As(III)), arsenate (As(V)), and their methylation metabolites, monomethylarsonate (MMA) and dimethylarsinate (DMA)) in urine should be used.Morning urine samples of 288 Dutch adults (aged 52–91 years) were analysed for As(III), As(V), MMA, DMA, arsenobetaine (AsB) and total As using ICP-MS. The risk of chronic kidney disease (CKD) related to TRA exposure in participants was assessed. The estimated daily intake (EDI) of inorganic As (iAs) was calculated for each participant using food consumption and occurrence data, and the correlation between EDIs and urinary TRA concentrations was investigated.The detection frequency of the individual As species in urine was high (59–100 %). The median and 95th percentile concentrations (middle bound) were 0.24 and 0.77 µg As(III)/g creatinine, 0.12 and 0.74 µg As(V)/g creatinine, 0.96 and 2.54 µg MMA/g creatinine, 8.09 and 63.82 µg DMA/g creatinine and 8.69 and 166.15 µg AsB/g creatinine, respectively. For total As, the detection frequency was 93 %, with median and 95th percentile concentrations of 10.96 and 131.53 µg/g creatinine, respectively. For calculated TRA, the median and 95th percentile concentrations were 5.75 and 35.53 µg/g creatinine, with DMA being the major contributor (85 %). A human biomonitoring-toxicological value (HBM-TV) of 13.7 µg TRA/g creatinine in urine was derived to assess the risk of CKD, and the risk could not be excluded in approximately 11 % of participants. A weak positive association was found between participants’ iAs EDIs and urinary TRA concentrations (ρ = 0.16–0.24).This study has generated novel concentration data of As species in morning urine samples of older Dutch adults. The risk assessment results indicate potential concern based on the current exposure in this group of participants. Such findings could be confirmed in a more comprehensive study with a larger and more geographically diverse group of Dutch adults.